2019
DOI: 10.3390/nu11123002
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Microbiome in Critically Ill Patients: Role of Nutrition

Abstract: Critically ill patients have an alteration in the microbiome in which it becomes a disease-promoting pathobiome. It is characterized by lower bacterial diversity, loss of commensal phyla, like Firmicutes and Bacteroidetes, and a domination of pathogens belonging to the Proteobacteria phylum. Although these alterations are multicausal, many of the treatments administered to these patients, like antibiotics, play a significant role. Critically ill patients also have a hyperpermeable gut barrier and dysregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 116 publications
2
34
0
Order By: Relevance
“…It is shown that increased abundance of proteobacteria community in the gut might contribute to low-fat/high-sugar diet-induced liver damage and high-fat dietinduced psychiatric disorders in mice [39,40]. Proteobacteria is the dominant phyla in septic patients [41,42]. To determine the causal link between post-septic SD-induced aggravation of systemic in ammation and gut microbiome, pseudo germ-free mice were constructed as recipients receiving fecal microbiota from septic mice with or without SD.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that increased abundance of proteobacteria community in the gut might contribute to low-fat/high-sugar diet-induced liver damage and high-fat dietinduced psychiatric disorders in mice [39,40]. Proteobacteria is the dominant phyla in septic patients [41,42]. To determine the causal link between post-septic SD-induced aggravation of systemic in ammation and gut microbiome, pseudo germ-free mice were constructed as recipients receiving fecal microbiota from septic mice with or without SD.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are due to alterations in gut muscle contractions, secretion, and absorption. Gut microbiota disturbances and epithelial barrier disintegration are also involved (3)(4)(5). In this situation, early-onset and the proper amount of nutrition support are of great importance (6).…”
Section: Introductionmentioning
confidence: 99%
“…Enteral nutrition (EN) is regarded as the favored root of nutrition support, because it protects the gut barrier, modulates immune responses, and leads to a faster return of gut function. However, many critical care patients cannot receive EN due to tolerance problems (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of broad-spectrum antimicrobials on the microbiota, and the subsequent recovery process, have been well documented [10][11][12]. However, critical illness can have profound effects on feeding and energy intake [13], and respiratory complications may lead to low oxygen saturation and subsequent hypoxia, inducing disruption of the gut microbiota [14]. Furthermore, changes in the structure of the microbiota may exacerbate the disease state or alter the course of recovery [3,12,15].…”
Section: Introductionmentioning
confidence: 99%